Molecular mechanisms of aflatoxin neurotoxicity and potential neuroprotective agents - Chongshan Dai; Erjie Tian; Hui Li; Subhajit Das Gupta; Zhihui Hao; Zhanhui Wang; Tony Velkov; Jianzhong Shen (Food Science and Human Wellness)
Aflatoxins (AFTs) represent one of the most notorious classes of deadly mycotoxins produced by certain fungi that are found on agricultural crops. Aflatoxins are highly toxic to mammals and are known to cause a series of detrimental effects, including neuro-, hepato-, nephron-, and immuno-toxicity. In this original review we summarize the mechanisms of aflatoxin-induced neurotoxicity and the clinical potential of novel neuroprotective agents. Aflatoxin B1 (AFB1) is the most toxic congener among the 21 identified AFTs. Recent studies have shown that food borne exposure to AFB1 and/or its metabolites often leads to fatal neurotoxicity in animals and humans. Animal studies indicated that AFB1 exposure could induce abnormal behavioral changes, including anxiety, lethargy disorders, depression-like behavior, cognitive, learning and memory defects, and decreased feeding behavior. Mechanistically, AFB1 exposure has been associated with lipid peroxidation, ablation of non-enzymatic and enzymatic antioxidant defense systems and decreased neurotransmitter levels. AFB1 exposure has also been shown to induce DNA damage, apoptosis, pyroptosis, and mitochondrial dysfunction in the brain tissue. Several signaling pathways, including gasdermin D, toll like receptor 2 (TLR2), TLR4, Akt, NF-κB, ERK/MAPK, protein kinase C (PKC), and mitochondrial apoptotic pathways have been shown to participate in AFB1-induced neuronal or astrocyte cell death. Targeting these pathways by small molecules (e.g., quercetin, curcumin, and gallic acid, and dimethyl fumarate), Chinese herbal extracts (e.g., Artichoke leaf extract, Chelidonium majus ethanolic extract, pumpkin extract, and Crocus sativus L. tea), and probiotic supplements could effectively improve AFB1-induced neurobehavioral abnormalities and neurotoxicity. To date, the precise molecular mechanisms of AFB1-induced neurotoxicity and potential neuroprotective agents remain unclear. In the present review, the clinical manifestations, molecular mechanisms, and potential neuroprotective agents of AFB1-induced neurotoxicity are summarized in the broadest overview. It is most hopeful that this broad reaching review provides valuable insights and stimulates broader discussion to develop the effective neuroprotective agents against aflatoxins.